PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE DAN STRUKTUR KEPEMILIKAN TERHADAP PROFITABILITAS PERUSAHAAN (Studi pada perusahaan Manufaktur sektor Makanan dan Minuman yang terdaftar di BEI Periode 2010-2014) - Sembiring, Edi Gia Gunanta Ras; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine effect of good corporate governance and ownership structure of profitability company. Where two independent variable that is GCG consist of ( the size of the board commissioners and composition of independent board of commissioners) and Ownership Structure consist of (managerial ownership and institutional ownership) and one variable dependent that is profitability company consist of (ROA,ROE,ROI)This study uses secondary data from investment gallery of indonesia stock exchange in Jendral Sudirman street number 73 Pekanbaru, Riau. The selection of samples is carried out by purposive sampling, where the population of this research is the manufacture company sector Food and Beverages with six companies sampled along 2010-2014 years. And this research method is descriptive and quantitative by using program of SPSS 20.Data analysis using multiple linear regression where the result of this study show that the size of the board commissioners and composition of independent board of commissioners does not have a significant effect on ROA; managerial ownership and institutional ownership has a significant effect on ROA; the size of the board commissioners, composition of independent board of commissioners, managerial ownership and institutional ownership simultaneously does have a significant effect on ROA; that the size of the board commissioners and composition of independent board of commissioners does not have a significant effect on ROE; managerial ownership and institutional ownership does not have a significant effect on ROE; the size of the board commissioners, composition of independent board of commissioners, managerial ownership and institutional ownership simultaneously does not have a significant effect on ROE; the size of the board commissioners and composition of independent board of commissioners does not have a significant effect on ROI; managerial ownership and institutional ownership has a significant effect on ROI; the size of the board commissioners, composition of independent board of commissioners, managerial ownership and institutional ownership simultaneously does have a significant effect on ROI.Keywords : The size of the board commissioners, composition of independent board of commissioners, managerial ownership, institutional ownership, Return On Assets, Return On Equity,and Return On Investment